2022
DOI: 10.26442/00403660.2022.09.201837
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and obesity

Abstract: Obesity is an independent predictor of cardiovascular diseases (CVD), including heart failure (HF). Nevertheless, numerous studies have shown that patients with CVD who are overweight and slightly obese have a better short-term and moderate prognosis than thinner patients with CVD. This phenomenon has been called the obesity paradox. Understanding the obesity paradox is important in patients with HF, given the high prevalence of obesity in patients with HF. The article presents an overview of clinical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
1
0
0
1
Order By: Relevance
“…An observational study found a higher rate of heart failure in obese patients, which is the same result as our univariate MR [4,[21][22][23]. However, a large body of research has shown that individuals with obesity have a better prognosis than lean individuals with the same level of heart failure disease, which is known as obesity paradox [24][25][26].…”
Section: Discussionsupporting
confidence: 81%
“…An observational study found a higher rate of heart failure in obese patients, which is the same result as our univariate MR [4,[21][22][23]. However, a large body of research has shown that individuals with obesity have a better prognosis than lean individuals with the same level of heart failure disease, which is known as obesity paradox [24][25][26].…”
Section: Discussionsupporting
confidence: 81%
“…Обращает на себя внимание, что среди пациентов с неблагоприятным течением СНсФВ отмечалась тенденция к более частому наличию ожирения (p=0,08), что соответствует концепции сердечнососудистого континуума и метаболического синдрома в условиях инсулинорезистентности [24,25] гностического и прогностического потенциала при различных нозологиях [10]. В настоящем исследовании у пациентов с неблагоприятным течением СНсФВ регистрировался повышенный уровень маркера GDF-15.…”
Section: Discussionunclassified